Mutant Mouse Models of Autism Spectrum Disorders - Provenzano, Giovanni (IOS Press, 2012)
Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental diseases characterized by a triad of specific behavioral traits: abnormal social interactions, communication deficits and stereotyped or repetitive behaviors. Several recent studies showed that ASDs have a strong genetic basis, contributing to the discovery of a number of ASD-associated genes. Due to the genetic complexity of these disorders, mouse strains with targeted deletion of ASD genes have become an essential tool to investigate the molecular and neurodevelopmental mechanisms underlying ASD. Here we will review the most relevant genetic mouse models developed by targeted inactivation of ASD-associated genes, and discuss their importance for the development of novel pharmacological therapies of these disorders.